VD_FINDINFO Jug / 2019 / 358 vom 29. Mai 2019 - VD Tribunal cantonal (2019)
EXPULSIONDROIT PÉNAL, À VIE, RÉCIDIVEINFRACTION, CONTRAVENTION, INTÉRÊT JURIDIQUEMENT PROTÉGÉ | 105 CP, 66a bis CP, 66a CP, 66b CP